Russian grotesque realism the great reforms and the gentry decline - Kokobobo, Ani (The Ohio State University Press, 2018)
"A rereading of the Russian realist novel that proposes a hybrid genre, grotesque realism, to describe changes during the postreform era"...
Includes bibliographical references and index
Keywords: Geschichte 1869-1899; Russian fiction -- 19th century -- History and criticism; Grotesque in literature; Realism in literature; Gentry in literature; Das Groteske; Russisch; Realismus; Sozioökonomischer Wandel; Roman